2022
DOI: 10.3389/fvets.2022.735139
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Ruminant Farmers' Use of Sustainable Production Practices for Climate Change Adaptation and Mitigation in Enugu State, Nigeria

Abstract: A sustainable ruminant production system ensures economically viable livestock systems that meet the current and future demands of animal products as well as the environmental safety of current and future generations. The study analyzed the determinants of ruminant farmers' use of sustainable production practices for climate change adaptation and mitigation in Enugu State, Nigeria. Multistage sampling procedure was used to select ninety six (96) ruminant farmers that constituted the sample for the study. Semi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Through adaptation, livestock farmers respond to the rapidly changing animal production environment (Raghuvanshi and Ansari, 2016). They engage in measures that offer immediate relief from the devastating effects of climate change (Nwobodo et al, 2022). From the current study, farmers have adopted improvements in quality of feed and fodder.…”
Section: Discussionmentioning
confidence: 94%
“…Through adaptation, livestock farmers respond to the rapidly changing animal production environment (Raghuvanshi and Ansari, 2016). They engage in measures that offer immediate relief from the devastating effects of climate change (Nwobodo et al, 2022). From the current study, farmers have adopted improvements in quality of feed and fodder.…”
Section: Discussionmentioning
confidence: 94%
“…Regarding studies in sub-Saharan Africa (Western, Central, Eastern, and Southern Africa), some researchers incorporated multiple countries as their study area (Branca et al, 2021; Branca et al, 2022; Bryan et al, 2009; Kristjanson et al, 2012; Makate, Makate and Mango, 2017). Meanwhile, some researches have been done in a single country (Abi et al, 2019; Barbier et al, 2009; Musafiri et al, 2022; Rakotovao et al, 2021; Maggio, Mastrorillo and Sitko, 2022; Molua, 2022; Nwobodo et al, 2022; Samuel and Sylvia, 2019; Setsoafia, Ma and Renwick, 2022; Siulemba and Moodley, 2014; Wilk, Andersson and Warburton, 2013; Zeweld et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, Rakotovao et al (2021) utilized several scenarios related to agroecology in Madagascar and found that the practice can help increase smallholder farmers’ productivity and profitability in the long run while mitigating CC. Nwobodo et al (2022) found that economic benefits such as financial inclusion schemes can be considered to motivate Nigerian farmers to adopt a ‘greener’ practice. Moreover, the level of knowledge also influences farmers’ implementation of SAPs.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, limited access to veterinary care could potentially result in compromised animal welfare outcomes. Studies have reported that a lack of access to veterinary care may result in more frequent outbreaks of disease, increased economic loss, and poor understanding of best management practices ( 7 , 15 , 16 ). Inability to access veterinary care has been suggested to be one of the most significant animal welfare crises in the United States, presenting considerable problems for the health of livestock and companion animals ( 17–19 ).…”
Section: Introductionmentioning
confidence: 99%